2016
DOI: 10.1111/ped.12995
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic factors for acute encephalopathy

Abstract: Serum AST, ALT and LDH may be related to early diagnosis and prognosis, and should be carefully investigated in patients with encephalopathy. CSF tau protein could also be used as an indicator of poor prognosis in acute encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Elevated LDH is a consequence of tissue damage (Augoff et al 2015) and has been observed in various pathologies, such as encephalitis, ischemic stroke or head injuries (Valvona et al 2016). Moreover, LDH levels have also been correlated with acute encephalopathy and could be related to prognosis as a significant difference in serum LDH levels was observed between pediatrics patients with and without developmental regression following acute encephalopathy (Motojima et al 2016). Future research should evaluate if this association between serum LDH levels and DTI metrics in COVID-19 patients is related to neurological complications, such as encephalopathy, and if it is the case, whether it is a good predictor of outcome regarding neurological sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated LDH is a consequence of tissue damage (Augoff et al 2015) and has been observed in various pathologies, such as encephalitis, ischemic stroke or head injuries (Valvona et al 2016). Moreover, LDH levels have also been correlated with acute encephalopathy and could be related to prognosis as a significant difference in serum LDH levels was observed between pediatrics patients with and without developmental regression following acute encephalopathy (Motojima et al 2016). Future research should evaluate if this association between serum LDH levels and DTI metrics in COVID-19 patients is related to neurological complications, such as encephalopathy, and if it is the case, whether it is a good predictor of outcome regarding neurological sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…For the multivariate logistic regression analysis, it was necessary to remove the strongly correlated parameters. Since AST is reportedly a predictor of poor outcome in patients with AE and status epilepticus [15,[20][21][22], we selected the AST level as a reference parameter for blood tests and examined the correlations between the AST level and the other significant parameters. The serum ALT, LDH, CK, and Cre levels were positively associated with the AST level (i.e., the correlation coefficient between the AST and ALT levels was 0.839, p < 0.001; Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that age less than 1.5 years and a Glasgow Coma Scale score of 14 or less (Japan Coma Scale score of 1 or higher) were high risk factors for developing acute encephalopathy with biphasic seizures and late reduced diffusion 7 . Another report described significant differences between febrile seizures and acute encephalopathy in terms of serum liver enzyme levels 8 . In regard to the early seizure phase, there are no reports that differentiate between non-prolonged febrile seizures and acute encephalopathy.…”
Section: Discussionmentioning
confidence: 99%